2014
DOI: 10.1136/bmjopen-2013-004419
|View full text |Cite
|
Sign up to set email alerts
|

Association of napping and night-time sleep with impaired glucose regulation, insulin resistance and glycated haemoglobin in Chinese middle-aged adults with no diabetes: a cross-sectional study

Abstract: ObjectiveTo assess associations between napping and night-time sleep duration with impaired glucose regulation, insulin resistance (IR) and glycated haemoglobin (HbA1c).DesignCross-sectional study.SettingFujian Province, China, from June 2011 to January 2012.ParticipantsThis study enrolled 9028 participants aged 40–65 years. Data of 7568 participants with no diabetes were included for analysis. Type 2 diabetes was defined applying WHO criteria.Outcome measuresParticipants’ daytime napping and night-time sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…Studies appoint that napping is more prevalent among men. [7][8] On the other hand, some experts have found no significant results regarding sex. 9 The influence of education and family income on elderly napping seems to be unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies appoint that napping is more prevalent among men. [7][8] On the other hand, some experts have found no significant results regarding sex. 9 The influence of education and family income on elderly napping seems to be unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have underlined the association of sleep complaints and sleep duration with IR in non-diabetic middle-aged patients [12,13]. In our study, all the patients were referred to our hospital for sleep complaints, but only AHI was independently associated with IR, not the objective sleep duration (TST).…”
Section: Discussionmentioning
confidence: 76%
“…However, these analyzes, though showing the strong association between OSA and IR, did not take into account other potential confounding factors, such as duration, quality and fragmentation of sleep, snoring and daytime sleepiness as suggested by other studies [10,11]. Indeed, in large population-based studies in middle-aged individuals without diabetes, subjective sleep complaints, self-reported sleep duration and daytime napping have been associated with IR, though without an objective OSA diagnosis by nocturnal recording [12,13]. Also in non-diabetic older subjects, self-reported symptoms of sleep-disordered breathing are associated with IR and increased incidence of type 2 diabetes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have corroborated these findings and found that naps are more prevalent in men. [1][2] Currently, the labor situation has undergone changes and an increasing number of women are inserted in the labor market. This means that women, in addition to the eight-hour day's paid work, come home and face domestic chores.…”
Section: Resultsmentioning
confidence: 99%
“…There seems to be no gender difference in relation to the nap, with higher rates among elderly men. [1][2] However, another study found no significant difference between the sexes. 3 The prevalence of nap seems to increase with advancing age, 4 and older adults report more frequent naps when compared to younger ones.…”
mentioning
confidence: 94%